Diversity of Myxomycetes from Peru Part III: The high Andes and the altiplano - Treviño-Zevallos, Italo; García-Cunchillos, Iván; de Basanta, Diana Wrigley; Lado, Carlos (Phytotaxa, 2023)
The results obtained from a survey for Myxomycetes in the Peruvian Andes (between 3,000 and 5,000 m a.s.l.) are reported. This survey is based on 3,352 identifiable collections of myxomycetes, resulting from sampling carried out during six field expeditions of the Myxotropic Project, from moist chamber culture and the revision of deposited specimens in the HSP herbarium. In total, 178 taxa representing 31 genera were recorded. Ten species are considered new records for South America or the Neotropics, and 53 additional new records for Peru are reported. Notes and SEM micrographs of relevant species are included. The best-represented order was Physarales with 55% (99 species), followed by Trichiales (43 species), Stemonitidales (21 species), Cribrariales (14 species), and the least represented was Echinosteliales (1 species). The most diverse genera were Physarum and Didymium, with 43 and 24 spp., respectively. The most abundant species were Didymium nigrisporum, with 336 collections and Didymium difforme, with 156 collections. These data, together with those obtained at other elevations in the country and in the Southern Andes, confirm the high diversity of myxomycetes of Peru, show the biological value of the Andes Cordillera and highlight the vital role that it plays in the distribution of these microorganisms. The study confirms the striking differences between the species assemblages in different vegetation belts of the tropical Andes, with only 18% of the species recovered in all three studied areas in Peru.